Efeitos nasais da expansão rápida de maxila assistida cirurgicamente: revisão sistemática da literatura e ensaio clínico randomizado através de tomografia computadorizada de feixe cônico - Medeiros, José Rômulo de (2020)
In the diversity of facial deformities, transverse maxilla deficiency is the most prevalent. The main characteristics of this alteration are the presence of ogival palate, dental crowding, dental rotations and uni or bilateral posterior crossbite, with a deficit in the perimeter of the dental arch. The change is related to decreased patency of the upper airways and altered breathing patterns. Surgically assisted rapid maxillary expansion (SARME) is the main technique used to treat transverse maxillary deficiencies in patients with skeletal maturity, with or without pterygomaxillary disjunction (PD) during the surgical procedure. The effect of SARME, with or without PD, on the nasal cavity is still not well established in the literature. Thus, the present thesis has objectives divided into two chapters. In chapter 1, there was a systematic review of the literature, in two stages, based on PROSPERO, in order to investigate the effects of SARME on the nasal cavity, nasal septum and paranasal region. To locate the articles, a search strategy was used in nine databases and in the gray literature. The 8 selected studies included a total of 180 adult individuals and used analyzes using cone beam computed tomography, frontal cephalometric radiography, 3D photographs and acoustic rhinometry. The main outcomes assessed were nasal cavity volume (VCN), minimum cross-sectional area (ASTM) of the nasal cavity, positioning of the nasal septum, width of the nasal cavity and volume of the nose (in soft tissues). In chapter 2, a randomized, double-blind clinical trial was carried out, with the purpose of evaluating changes in the nasal cavity, including the nasal septum, after performing SARME with PD (group + DP) and without PD (PD group). Twenty-four patients of both sexes, aged 18 to 45 years, equally divided into the two groups allowed a representative sample with 80% power and 95% confidence. The primary end point adopted for the present study was the nasal width, while the secondary end points were the angular alteration of the nasal septum, measurements of nasolabial soft tissues and the analysis by superimposing images.The software 3D Slicer (version 4.6.2) and ITK-Snap (version 3.6.0) were used for the volumetric measurements of the nasal cavity, angular of the nasal septum and by superimposing images. Nasal soft tissues were also evaluated using Dolphin Imaging 3D® software. The evaluations were performed in the immediate preoperative period (T1), immediately after the end of the expansion (T2) and six months after the surgery (T3). SARME surgeries provided a statistically significant increase in hard tissues, regarding the width of the lateral wall of the nasal cavity (LNR-L), with p-value <0.001; in the group - PD and p-Value = 0.009; in the + PD group, and at the level of the anterior nasal spine (ENAR-L), with p-Value <0.001; in both groups, with minimal and non-significant soft tissue repercussions, after 6 months of Hyrax locking, thus, PD did not influence these outcomes and should not be indicated in order to increase the dimensions of the width of the lateral wall of the cavity nasal. PD provided less amount of nasal septum movement as compared to Yaw (p-value = 0.025), so it could be indicated in patients who already have deviated septum, without functional implications, in order to avoid the possibility of injury deviation and functional worsening of respiratory permeability in the nasal valve region. The present study also concluded that the amount of expansion that remains after 6 months of locking Hyrax in the nasal floor region, at the level of the canines and upper second molars, is very small, confirming the already known “V” pattern, and who was not influenced by PD. The findings of the present study suggest that further research with a design similar to the one used in this work would be interesting so that the data obtained from CT scans from different studies can be correlated; it would also be important that research involving clinical and functional parameters can be compared to tomographic findings in future studies.